Konstruksi Isu Lingkungan di Media Indonesia - Serin Himatus Soraya; Sri Mulyani (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2025)
This study aims to analyze how online media in Indonesia construct environmental issues through different perspectives of values ​​and ideologies. The two media outlets studied are NU Online, a representative of Islamic da'wah-based media, and Kumparan.com, a representative of general media based on digital journalism. This study uses Agenda Setting theory (McCombs & Shaw, 1972) to explore two levels of analysis: issue salience (the determination of the issue agenda) and attribute salience (the formation of meaning and values). The method used is qualitative content analysis with a descriptive-comparative approach to ten environmental articles published between September and October 2025. The results show that NU Online frames environmental issues within an Islamic ecotheological framework, emphasizing the values ​​of amanah (trust), khalifah (vicegerent), mizan (property), and ihsan (goodness) as the moral basis for preserving nature. Meanwhile, Kumparan.com emphasizes a technocratic and collaborative approach, addressing ESG issues, SDGs, and green innovation as a sustainable development strategy. Both media play a role in shaping public ecological awareness, but with different value orientations: spirituality in Islamic media and rationality in mainstream media. This research contributes to strengthening the media's role in building ethical, reflective, and sustainable public ecological awareness in Indonesia.